Predictors of home-based cardiac rehabilitation exercise adherence among patients with chronic heart failure: a theory-driven cross-sectional study - Zhen Yang; Honghong Jia; Aiping Wang (BMC, 2023)
Abstract Background The factors influencing home-based cardiac rehabilitation exercise adherence among patients with chronic heart failure remain unclear. This study aimed to explore predictors of home-based cardiac rehabilitation exercise adherence in these patients, based on the theory of planned behavior. Methods This theory-driven, cross-sectional study used convenience sampling to recruit patients with chronic heart failure undergoing home-based cardiac rehabilitation. Instruments used included the Home-Based Cardiac Rehabilitation Exercise Adherence Scale, the Multidimensional Self-Efficacy for Exercise Scale, the Perceived Social Support Scale, and the Tampa Scale for Kinesiophobia Heart. Multivariate linear hierarchical regression analysis was employed to examine the factors influencing exercise adherence. Results A total of 215 patients with chronic heart failure undergoing home-based cardiac rehabilitation participated in the study. The overall score for home cardiac rehabilitation exercise adherence was (48.73 ± 3.92). Multivariate linear hierarchical regression analysis revealed that age (β=-0.087, p = 0.012), education level (β = 0.080, p = 0.020), fear of movement (β=-0.254, p < 0.001), perceived social support (β = 0.451, p < 0.001), and exercise self-efficacy (β = 0.289, p < 0.001) influenced home-based cardiac rehabilitation exercise adherence. In the second model, fear of exercise explained 23.60% of the total variance, while perceived social support and exercise self-efficacy explained 26.60% of the total variance in the third model. Conclusion This study found that home-based cardiac rehabilitation exercise adherence in patients with chronic heart failure was suboptimal, and identified its influencing factors. Targeted interventions addressing these factors, such as tailored education, support, and addressing fear of exercise, may help improve exercise adherence.